2016 IEEE International Parallel and Distributed Processing Symposium Workshops (IPDPSW) 2016
DOI: 10.1109/ipdpsw.2016.114
|View full text |Cite
|
Sign up to set email alerts
|

A Multi-Platform Evaluation of the Randomized CX Low-Rank Matrix Factorization in Spark

Abstract: Abstract-We investigate the performance and scalability of the randomized CX low-rank matrix factorization and demonstrate its applicability through the analysis of a 1TB mass spectrometry imaging (MSI) dataset, using Apache Spark on an Amazon EC2 cluster, a Cray XC40 system, and an experimental Cray cluster. We implemented this factorization both as a parallelized C implementation with hand-tuned optimizations and in Scala using the Apache Spark highlevel cluster computing framework. We obtained consistent pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In the current GstLAL pipeline, streamer multi-media framework has been used and HTC based distributed set-up is developed to run all the steps involved in this pipeline [7]. In recent work, Gittens et al [47] showed the adaptability of RMF algorithm in a Apache-SPARK set-up. SPARK-optimized code with enhanced computation power, making our algorithms much faster.…”
Section: Discussionmentioning
confidence: 99%
“…In the current GstLAL pipeline, streamer multi-media framework has been used and HTC based distributed set-up is developed to run all the steps involved in this pipeline [7]. In recent work, Gittens et al [47] showed the adaptability of RMF algorithm in a Apache-SPARK set-up. SPARK-optimized code with enhanced computation power, making our algorithms much faster.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, a non-naïve version of this meta-algorithm is very promising: it gives the best worst-case algorithm in RAM [164,69,71] (using Sketch-and-Solve, described below); it beats LAPACK for high precision in wall-clock time [157,9,134] (using Sketch-and-Precondition, described below); it leads to super-terabyte-scale implementations in parallel/distributed environments [174,85]; and it gives the foundation for low-rank approximations and the rest of RandNLA [72,73,124,68]. Fundamental structural result.…”
Section: Least-squares Approximationmentioning
confidence: 99%